Role of the Zinc Finger Transcription Factor SltA in Morphogenesis and Sterigmatocystin Biosynthesis in the Fungus Aspergillus nidulans - Shantappa, Sourabha (Public Library of Science, 2013)

(untitled)
Potassium, a widely accepted macronutrient, is vital for many physiological processes such as regulation of cell volume, maintenance of intracellular pH, synthesis of proteins and activation of enzymes in filamentous fungi. Another cation, calcium, plays an essential role in many signaling processes from lower to higher eukaryotes. Imbalance in the intracellular ionic levels of potassium or calcium causes adverse effects on cell growth, morphology and development, and eventually death. Previous studies on the adaptation of Aspergillus nidulans to salt and osmotic stress conditions have revealed the role of SltA, a C(2)H(2) zinc finger transcription factor in cation homeostasis. SltA is highly conserved in the Ascomycota phylum with no identifiable homolog in S. cerevisiae and other yeast-like fungi, and prevents toxicity by the cations Na(+), K(+), Li(+), Cs(+) and Mg(2+), but not by Ca(2+). However its role in morphology and biosynthesis of natural products such as mycotoxins remained unknown. This study shows the first characterization of the role of calcium and SltA fungal homologs in morphogenesis using the model system A. nidulans. Addition of potassium to sltA deletion mutants resulted in decreased levels of sterigmatocystin production. A similar phenotype was observed for both types of mutants in veA1 and veA (+) genetic background. Expression of the sterigmatocystin genes aflR and stcU was strongly reduced in sltA deletion mutant when K(+) was added. Additionally, increased concentrations of K(+) drastically reduced sexual and asexual development, as well as radial growth in deletion sltA colonies. This reduction was accompanied by lower expression of the morphology related genes nsdD, steA and brlA. Interestingly, addition of calcium was able to stimulate asexual and sexual development and remediate the deletion sltA phenotype, including defects in morphology and toxin production.